Hubungan Oksigenasi dengan Kejadian Shivering Pasien Spinal Anestesi Di RSUD Prof.Dr. Margono Soekarjo Purwokerto - Uji Sigit Prasetyo; Sugeng Sugeng; Ana Ratnawati (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2017)
The incidence of shivering varies between 5% – 65 %. Shivering causes adverse physiological effects such as peripheralvasoconstriction, compensation of increasing oxygen requirement up to 5 times will increase carbon dioxide production,lowering arterial oxygen saturation, decreasing drug metabolism, disturbing blood coagulation factor, lowering immuneresponse, impairing wound healing, increasing protein breakdown, and ischemic of heart muscle. This study aims todetermine relationship between oxygenation with shivering incidence among spinal anaesthesia patients at Prof. Dr.Margono Soekarjo Hospital, Purwokerto. This research was an analytic observational research with cross sectionalapproach. Population in this study was all patients with spinal anesthesia at Dr. Margono Soekarjo Hospital, Purwokerto, withthe total of 50 patients. Sampling method using purposive sample, obtained 45 respondents. Data were analyzed using chisquaretest. Most of patients under spinal anesthesia at Dr. Margono Soekarjo Hospital, Purwokerto were giving oxygenationmore than 2 lt/minas many as 25 patients (55.6%). Most of patients under spinal anesthesia were not experience shivering incidence as manyas 33 patients (73.3%). There is a relationship between oxygenation and shivering incidence among patients under spinalanaesthesia at Dr. Margono Soekarjo Hospital, Purwokerto (p value = 0.000).